D-dimer for the prediction of left atrial appendage thrombosis: daydream or reality? A meta-analysis. (25th November 2020) - Casula, M; Fortuni, F; Frassica, R; Coccia, M.G; Magrini, G; Fabris, F; Gnecchi, M; Leonardi, S; Savastano, S; Rordorf, R
Abstract: Introduction: Left atrial appendage thrombosis (LAAT) is a dangerous condition that mainly affects patients with atrial fibrillation (AF) or those with mitral stenosis (MS), increasing their risk of stroke. Transesophageal echocardiography (TEE) is the gold standard for the diagnosis of LAAT but some technical issues and the suboptimal sensitivity in identifying small thrombi, especially within a side lobe, can limit its clinical usefulness. Reliable non-invasive diagnostic methods could be useful in clinical practice. D-dimer, a fibrin degradation product already commonly used in the diagnostic work-up of conditions such as venous thromboembolism, may have a role as a non-invasive marker of LAAT. Purpose: To evaluate the diagnostic performance of D-dimer for the detection of LAAT in patients with AF and/or MS, using TEE as the reference standard. Methods: We searched the literature for studies that evaluated the ability of D-dimer to predict LAAT. For each study a 2x2 table of D-dimer positivity and LAAT presence was constructed. Sensitivity, specificity, positive predictive value and negative predictive value were calculated. Considering the different diagnostic thresholds used in the included studies, the overall sensitivity and specificity were calculated using a hierarchal summary receiver operating characteristic (HSROC) model and a SROC curve was generated. Results: 6 studies, evaluating 1380 patients of whom 154 had LAAT, were included in the analysis. The prevalence of LAAT in the studies ranged from 9% to 26%, with a median of 12%. The mean age was 60±13 years, 63% were male. The mean left atrial diameter was 43±3 mm. The D-dimer diagnostic threshold ranged from 200 mcg/l to 1150 mcg/l. The overall sensitivity calculated with the HSROC model was 85%±28% and the overall specificity was 82%±29%. The negative predictive value was 98%. Figure 1 shows the summary ROC curve: individual studies are depicted by a clear circle; the red circle marks the pooled sensitivity and specificity across the 6 studies. The red dot-dashed-curve marks the boundary of the 95% credible region for the pooled estimates of sensitivity and specificity. Conclusions: Our analysis shows that D-dimer has a good diagnostic performance with a very high negative predictive value for LAAT and therefore it might be of clinical aid for ruling out the presence of LAAT in patients with AF and/or MS. Further studies are needed to determine the best diagnostic threshold. Funding Acknowledgement: Type of funding source: None